Writing permitted in designated areas only - Brodkey, Linda (Pedagogy and cultural practice, 1996)
Ranging from personal essay to hard-hitting polemic and touching on many of the major issues in the teaching of writing today, this volume explores alternatives to the standard methods for teaching composition.